2021
DOI: 10.1002/cbdv.202100221
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antioxidant Capacity of Some Derivatives of Sesamol at the C‐6 Position

Abstract: Several synthetic approaches (aminomethylation, alkylation, condensation, etc.) have been used to synthesize derivatives based on the sesamol (1), natural phenol. The set of methods, including the study of antioxidant activity (AOA) by the ability to inhibit the initiated oxidation of animal lipids, radical scavenging activity, Fe2+‐chelation ability, as well as a comparative assessment of membrane‐protective activity under the conditions of H2O2‐induced hemolysis of mice red blood cells (RBCs), was used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
2
1
0
Order By: Relevance
“…RSA determination was based on the ability of derivatives 1 – 6 to neutralize the DPPH radical, and TAA determination was based on the reduction of Mo(VI) to Mo(V) at acidic medium with formation of a colored phosphomolybdenum complex. The study demonstrated that α‐mangostin ( 1 ) functionalization increases the RSA of its derivatives 2 – 6 by a factor of 2.4–3.6 ( p =0.021), which is consistent with our previous findings for aminomethyl derivatives of xanthones [7b] and sesamol [7d] . Compounds 2 – 5 containing methoxyphenyl fragments were more active than derivative 6 ( p =0.004).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…RSA determination was based on the ability of derivatives 1 – 6 to neutralize the DPPH radical, and TAA determination was based on the reduction of Mo(VI) to Mo(V) at acidic medium with formation of a colored phosphomolybdenum complex. The study demonstrated that α‐mangostin ( 1 ) functionalization increases the RSA of its derivatives 2 – 6 by a factor of 2.4–3.6 ( p =0.021), which is consistent with our previous findings for aminomethyl derivatives of xanthones [7b] and sesamol [7d] . Compounds 2 – 5 containing methoxyphenyl fragments were more active than derivative 6 ( p =0.004).…”
Section: Resultssupporting
confidence: 90%
“…The difference in the prooxidant and antioxidant properties of various free radical modulators may be due to the experimental model, the primary target of the oxidation inducer, the presence of catalytic metal ions, and the antioxidant/oxidation substrate concentration ratio [15d,e,23] . This finding was corroborated in a number of our previous studies on biological activity of other compounds, such as allylpolyalkoxybenzenes, [9] curcumin, [24] and sesamol‐based methylenebisphenol [7d] …”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation